The Ruby on Rails tutorial : learn Web development with Rails ([Addison-Wesley Professional], 2016)
"Best-selling author and leading Rails developer Michael Hartl teaches Rails by guiding you through the development of three sample applications of increasing sophistication, focusing on the fundamental techniques in web development needed for virtually any kind of application. The updates to this edition include full compatibility with Rails 5 and numerous new exercises interspersed in each lesson for maximum reinforcement. This indispensable guide provides integrated tutorials not only for Rails, but also for the essential Ruby, HTML, CSS, and SQL skills you need when developing web applications. Hartl explains how each new technique solves a real-world problem, and then he demonstrates it with bite-sized code that's simple enough to understand, yet useful."--Resource description page.